A Novel Stimuli‐Responsive Injectable Antibacterial Hydrogel to Achieve Synergetic Photothermal/Gene‐Targeted Therapy towards Uveal Melanoma. Issue 18 (31st July 2021) - Wang, Shaoyun; Chen, Baohui; Ouyang, Liping; Wang, Donghui; Tan, Ji; Qiao, Yuqin; Ge, Shengfang; Ruan, Jing; Zhuang, Ai; Liu, Xuanyong; Jia, Renbing
Abstract: Uveal melanoma (UM) is the most prevalent primary intraocular malignant tumor with a high lethal rate. Patients who undergo conventional enucleation treatments consistently suffer permanent blindness, facial defects, and mental disorders, therefore, novel therapeutic modalities are urgently required. Herein, an injectable and stimuli‐responsive drug delivery antibacterial hydrogel (CP@Au@DC_AC50) is constructed via a facile grinding method that is inspired by the preparation process of traditional Chinese medicine. The incorporation of gold nanorods can enhance the mechanical strength of the hydrogel and realize photothermal therapy (PTT) and thermosensitive gel‐sol transformation to release the gene‐targeted drug DC_AC50 on demand in response to low‐density near‐infrared (NIR) light. The orthotopic model of UM is built successfully and indicates the excellent efficiency of CP@Au@DC_AC50 in killing tumors without damage to normal tissue because of its synergistic mild temperature PTT and gene‐targeted therapy. Moreover, the eyeball infection model reveals the remarkable antibacterial properties of the hydrogel which can prevent endophthalmitis in the eyeball. There is negligible difference between the CP@Au@DC_AC50+NIR group and normal group. This NIR light‐triggered gene‐targeted therapy/PTT/antibacterial treatment pattern provides a promising strategy for building multifunctional therapeutic platform against intraocular tumors and exhibits great potential for the clinical treatment of UM. Abstract : Inspired by the grinding method in traditional Chinese medicine preparation, the injectable antibacterial self‐assembling nanofiber CP@Au@DC_AC50 hydrogels are first constructed. NIR light‐triggered drug release/photothermal/gene‐targeted therapy of CP@Au@DC_AC50 exhibits brilliant synergistic antitumor and antibacterial efficiency without damage to intraocular tissue in vitro and in vivo. The gene‐targeted therapy/PTT/antibacterial platform has potential for future application in ocular tumor therapy.